Relationship of Family Economic Status to Complete Basic Immunization Coverage - Gede Wirabuana Putra; Rus Andraini (Miracle Journal Get Press, 2025)
Complete basic immunization is a key public health intervention to prevent infectious diseases in children. However, coverage remains suboptimal in parts of Indonesia, including Padang. One factor influencing this is family economic status, which can impact access, awareness, and compliance with immunization programs. Purpose: This study aimed to analyze the relationship between family economic status and complete basic immunization coverage among children aged 12–24 months in the Ambacang Health Center working area, Padang. Methods: A quantitative cross-sectional design was used. The sample included 50 mothers with children aged 12–23 months, selected through purposive sampling. Data were collected using structured questionnaires and immunization records, and analyzed using the Chi-square test. Results: Of the respondents, 58% came from low-income families, while 42% were from middle-to-upper economic backgrounds. The coverage of complete basic immunization was 66%. Statistical analysis showed a significant relationship between family economic status and immunization coverage (p = 0.021). Children from higher-income families were more likely to be fully immunized. Implications: These findings underscore the need for public health programs to consider socioeconomic factors when planning interventions. Targeted education and improved access to immunization services are especially needed for low-income communities. Conclusion: There is a significant correlation between family economic status and complete basic immunization coverage, highlighting the importance of equity-based approaches in immunization programs.